A Variation of the q-Painlevé System with Affine Weyl Group Symmetry of Type E₇⁽¹⁾ - Nagao, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
Recently a certain q-Painlevé type system has been obtained from a reduction of the q-Garnier system. In this paper it is shown that the q-Painlevé type system is associated with another realization of the affine Weyl group symmetry of type E₇⁽¹⁾ and is different from the well-known q-Painlevé system of type E₇⁽¹⁾ from the point of view of evolution directions. We also study a connection between the q-Painlevé type system and the q-Painlevé system of type E₇⁽¹⁾. Furthermore determinant formulas of particular solutions for the q-Painlevé type system are constructed in terms of the terminating q-hypergeometric function.